Seasonal changes in the food supply, numbers and male plumages of Pigmy Geese on the Thamalakane river in northen Botswana - Douthwaite, R J (Wildfowl, 1980)
Monthly counts of Pigmy Geese Nettapus auritus were made along 4 km of the Thamalakane river in northern Botswana between December 1977 and March 1979. The species was migratory, highest counts (138, 125) being made in December and lowest (1, 2) in March and April. Ripe fruits of the water-lily Nymphaea caerulea, its principal food, were most abundant from late September to January and scarcest from June to early September, but fluctuations in the numbers of geese were probably related more to the suitability of the area for breeding, and its unsuitability for wing-moult, than to changes in the food supply. The population in the Okavango Delta may number 5,000-15,000 birds. The sex ratio in the counts was 162 males:100 females. Excluding counts made in December and January, the proportion of males increased with population size. Males in southern Africa probably assume an eclipse plumage for part of the period April to October.